Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Tentang Menopause Pada Ibu-ibu PKK Dukuh Menjing RT 03 Donohudan Ngemplak Boyolali - Putri, Dita Rahmawati; , Dr. Faizah Betty Rahayuningsih, A. S. Kep., M. Kes (2017)
Menopause is the final phase or the cessation of ovulation and menstruation in women. Women's knowledge of the physiological, psychological and sexual changes of menopause is lacking. In addition, the officers at Posyandu said that there has never been a health education about menopause and PKK mothers Haming Menjing RT 03 Donohudan also not understand the climacterium phase, the stages of menopause, the cause of menopause, the characteristics of physical changes in menopause, the characteristics of psychological changes in Menopause, signs and symptoms, menopausal complications, prevention of negative effects of menopause. This study aims to determine the effect of health education on knowledge about menopause. This research method is pre experimental research with one group pre-post test design design. This research was conducted at Hamlet Menjing RT 03 Donohudan Ngemplak Boyolali. Samples were taken from 35 mothers with purposive sampling sampling technique. The instrument used is a questionnaire knowledge about menopause. Test to know the data analysis using paired simple t-test. The results showed that the average pre test score of knowledge of PKK women before being given health education about menopause was 62,14. While the average value of post test of knowledge of PKK mothers after given health education equal to 74,57. Then the increase of 12.43 with a significant value of 0,000 where ρ <0.05 then H0 is rejected. The conclusion of this research is there is influence of health education to knowledge about menopause at PKK Ladies of Menjing RT Community 03 Donohudan Ngemplak Boyolali. Conclusion shows there is influence of health education to knowledge about menopause at PKK lady Hamlet Menjing RT 03 Donohudan Ngempalak Boyolali. Suggestions for health workers need to improve health education programs with different methods and media. Researchers can further increase knowledge while providing information about health education about menopause with different methods and media. So as to provide convenience to the next research and provide better results.